Advancing Resilience and Fostering Sustainable Development through Strategic Investments in Cutting-Edge Technology and Innovative Methodologies for Disaster Risk Reduction: Japan Experiences - Naura Lulu Farhanrika; Sarpono Sarpono; Kusuma Kusuma; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
This research paper explores Japan's experiences in advancing resilience and fostering sustainable development through strategic investments in cutting-edge technology and innovative methodologies for disaster risk reduction. Japan, a country prone to natural disasters, has developed a comprehensive approach that encompasses strong governance, continuous learning, community empowerment, public awareness, and international collaboration. Through a mixed-method research methodology incorporating qualitative and quantitative analyses, this study examines Japan's robust disaster risk reduction framework and the role of cutting-edge technology in mitigating the impacts of hazards. The findings highlight Japan's multi-hazard approach, stringent building codes, and resilient infrastructure, which have significantly reduced disaster risks. The integration of innovative methodologies, such as community empowerment and early recovery planning, has fostered resilience at the grassroots level. Furthermore, the research showcases Japan's use of advanced technologies including early warning systems, remote sensing, and geospatial technologies. The lessons learned from Japan's experiences provide valuable insights for countries seeking to enhance their disaster risk reduction efforts and promote sustainable development. By investing in cutting-edge technology and adopting innovative methodologies, countries can effectively reduce disaster risks, build resilience, and foster sustainable development in the face of evolving challenges and hazards.